The Utilization of Artifical Intelligence in Optimizing Digital Marketing Strategies in Start-Up Companies - Adista Anjar Diany; Taqwa Sultan (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the use of artificial intelligence (AI) in optimizing digital marketing strategies in start-ups. The research uses a qualitative approach with case study methods in several startup business sectors, such as e-commerce and fintech. Data was obtained through in-depth interviews, observations, and documentation analysis. The results show that the application of AI contributes significantly in five main aspects, namely: (1) personalization of services and user experience, (2) budget efficiency and campaign optimization, (3) increased interaction with customers through chatbots, (4) implementation challenges in the form of limited human resources, high initial investment costs, and data privacy issues, and (5) adaptation strategies carried out by companies through collaboration with AI service providers, internal training, as well as gradual technology investment. These findings confirm that AI has become a strategic instrument for start-ups to increase competitiveness, although its application still faces various limitations. This research contributes to the digital marketing literature by emphasizing the importance of a balance between the use of technology and adaptive strategies that are appropriate to the conditions of startups.